Objective of the system of the state of Ukraine: contents, characteristics, importance for law enforcement activities - Оболенцев, Валерий Федорович (Theory and practice of jurisprudence, 2019)
For the proper functioning of the system of the state of Ukraine, it is necessary to determine its fundamental guidelines. In the article on the basis of methodology of systematic analysis the purpose of the system of the state of Ukraine is substantiated. It examines its compliance with the requirements that apply to the purpose of system objects. The comments on the interpretation of the purpose of the system of the state of Ukraine set out in the Constitution and other normative documents of the Ukrainian legislation are given. The main qualitative requirements for the purpose of the system are: 1) validity; 2) certainty; 3) reach; 4) the ability to determine the degree of achievement of the goal; 5) time orientation The main qualitative requirements for the purpose of the system are: 1) validity; 2) certainty; 3) reach; 4) the ability to determine the degree of achievement of the goal; 5) time orientation. Goal setting enables: - orient the elements of the system in personal, social and economic space; - mobilize and effectively use system resources; - to control the functioning of the system; - increase the validity of the evaluation of results activities Тhe purpose of the Ukrainian state system is human rights and freedoms.